The commodification of alternative cultural spaces - do Carmo, Letícia Cabeçadas; Pattaroni, Luca (Street Art & Urban Creativity, 2018)
The commodification of “alternative” cultural spaces is a process that has started to take place in several European cities, like Lisbon, for instance. This has happened due to the pressure of the real estate market, tourism trends or the austerity measures imposed by Troika, during the global economic crisis (2008). It is in this context that a specific real estate agency acts in order to create an opportunity for its business, investing in the rehabilitation of buildings and revitalization of certain areas of the city (interstices), supported by decorative aesthetics and an architectural design inspired by cultures of resistance. This strategy of territorial and decorative investment has had a big impact in the city of Lisbon. The reuse of images, buildings and practices related to “alternative” environments leads to the aesthetization of certain architectures – particularly those which host creative and cultural projects, and whose designs and marketing strategies distort political or social meanings.